Humanity. - Ai, Weiwei (Book collections on Project MUSE., 2018)
Writings on human life and the refugee crisis by the most important political artist of our timeAi Weiwei (b. 1957) is widely known as an artist across media: sculpture, installation, photography, performance, and architecture. He is also one of the world's most important artist-activists and a powerful documentary filmmaker. His work and art call attention to attacks on democracy and free speech, abuses of human rights, and human displacement--often on an epic, international scale. This collection of "ations demonstrates the range of Ai Weiwei's thinking on humanity and mass migration, issues that have occupied him for decades. Selected from articles, interviews, and conversations, Ai Weiwei's words speak to the profound urgency of the global refugee crisis, the resilience and vulnerability of the human condition, and the role of art in providing a voice for the voiceless. Select "ations from the book:"This problem has such a long history, a human history. We are all refugees somehow, somewhere, and at some moment."Allowing borders to determine your thinking is incompatible with the modern era." "Art is about aesthetics, about morals, about our beliefs in humanity. Without that there is simply no art." "I don't care what all people think. My work belongs to the people who have no voice."